Performance of Barangay Police Security Officers: Developing Interventions - Turno, Cheribel S.; Bildo, Jessa M.; Lahiban, Jubilee Jean P.; Perino, Lara I.; Romero, Princess Raquiza T. (Universitas Muhammadiyah Yogyakarta, 2023)
The Barangay Police Security Officers (BPSO) perform voluntary services to maintain peace and order in their communities. The BPSOs encountered challenges in performing their duties and responsibilities, which could be improved through appropriate interventions. This study determined the BPSOs' level of performance in carrying out their duties and responsibilities, the difficulties they faced, and the interventions that would assist them in performing consistently. The study used a descriptive design and quantitative and qualitative methods to gather data. Descriptive involves gathering or collecting data by describing events and organizing, tabulating, depicting, and describing the data collection. This concluded that BPSO attained the DILG MC 2003-42 guidelines, where the assigned task was successfully executed and achieved the established standard, resulting in outstanding performance. Therefore, the BPSOs, in performing their duties and responsibilities, have encountered a lot of challenging tasks in which they are committed to taking risks to maintain peace and order in the community. The researchers develop an intervention to help provide governments with input in addressing the BPSO concerns. This study would be helpful to the DILG, LGU, PNP, barangay authorities, BPSO, residents, and upcoming researchers. They would benefit from the interventions and recommendations that would enhance the BPSO's effectiveness in upholding peace and order.